Perceived Service Quality and User Satisfaction with Orthotic-Prosthetic Devices and Services Among Individual with Physical Disabilities - Utami, Feryanda; Argianto, Argianto (Indonesian Journal of Disability Studies, 2023)
This research contributes to ongoing efforts to enhance healthcare service quality and improve the well-being of individuals with disabilities, particularly those with physical disabilities relying on orthotic-prosthetic care in their communities. Currently, there is limited evidence available to guide policy, funding decisions, and practitioners in Indonesia. Study participants included adult orthosis/prosthesis users and parents/guardians of children using these devices, all of whom sought services at the Jakarta I Ministry of Health Polytechnic educational clinic in January to June 2023. Subsequently, the socket fabrication, fitting, and evaluation process took place, utilizing purposive sampling for surveys encompassing demographics and the Modified Orthotic Prosthetic User Survey (OPUS) – Client Satisfaction with Devices and Services. 73% of patients reported satisfaction with high-quality Orthotic-Prosthetic devices, while 86% expressed satisfaction with excellent service. This highlights the effectiveness of the Modified Orthotic Prosthetic User Survey (OPUS) in assessing user satisfaction with prosthetic-orthotic devices and services, underscoring the need for ongoing tool refinement.